The Effect of Performance Measurement on Product Innovation, with Leadership Style as A Moderating Variable - Retalia Risma Sari (Cakrawala Repositori IMWI)
Product innovation has become an essential capability for manufacturing companies to maintain competitiveness in an increasingly dynamic market environment. However, achieving sustainable innovation requires effective managerial mechanisms, including the implementation of performance measurement systems and appropriate leadership approaches. This study aimed to examine the effect of performance measurement on product innovation and analyze the moderating role of leadership style in strengthening the relationship between performance measurement and product innovation. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 100 respondents consisting of business owners and production managers from manufacturing companies in Jember Regency, East Java. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that performance measurement had a positive and significant effect on product innovation, with a path coefficient of 0.373 and a significance value of 0.000. Furthermore, leadership style significantly moderated the relationship between performance measurement and product innovation, as demonstrated by an interaction coefficient of 0.602 and a significance value of 0.000. The structural model explained 68.4% of the variance in product innovation, indicating strong predictive capability. These findings indicate that performance measurement functions not only as an evaluation instrument but also as a strategic mechanism for encouraging innovation activities. This study contributes to the management literature by emphasizing the importance of integrating performance measurement systems and leadership styles to strengthen innovation capabilities within manufacturing organizations.